La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)
fs-ref-orig: Bouchard, L., Batal, M., Imbeault, P., Gagnon-Arpin, I., Makvandi, E., & Sedigh, G. (2012). The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS). Réseau de recherche appliquée sur la santé des francophones de l'Ontario. fs-code-orig: Bouchard-2012d

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)

Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est - Bouchard, Louise; Gagnon-Arpin, Isabelle; Makvandi, E.wa (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)
fs-ref-orig: Bouchard, L., Gagnon-Arpin, I. et Makvandi, E. (2012). Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est. Réseau de recherche appliquée sur la santé des francophones de l’Ontario. fs-code-orig: Bouchard-2012e

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 5 - Description des expériences de trajectoires individuelles de soins de santé en français pour les aînés | Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 5 - Description of experiences of seniors' individual trajectories in French-language health care - Éthier, Sophie; Ba, Halimatou; Belzile, Louise; Gagné, Maryanne; Roch-Gagné, Margaux (Conseil communauté en santé du Manitoba et Université de Saint-Boniface, 2012)

La prise en compte de la langue dans les foyers de soins pour personnes âgées - Forgues, Éric; Gaucher, Charles; Guignard Noël, Josée; Kabano, John; Michaud, Jacques (Institut canadien de recherche sur les minorités linguistiques, 2012)

Impact de la situation linguistique minoritaire sur les soins de santé pour les personnes âgées francophones de l’Ontario souffrant de maladies chroniques : partage des connaissances et rétroaction. Rapport de recherche - Lemonde, Manon; Boudreau, Françoise; Dufour, Suzanne (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Francophones living with HIV/AIDS in Ontario: The unknown reality of an invisible cultural minority - Samson, Andre. A.; Spector Noah. M. P. (AIDS Care, 2012)
A strong body of evidence demonstrates that education, prevention and intervention, in the context of HIV/AIDS, should take ethno-racial diversity into account. The current research focuses on the cultural sensitivity manifested by AIDS service organisation ASO professionals towards Francophone minority persons living with HIV/AIDS Francophone PHAs in the two main urban centres of Ontario: Ottawa and Toronto. More specifically, this qualitative research will describe two different points of view: Francophone PHA service users n17 and ASO professionals n12. Data were collected from multiple focus groups and analysed using a phenomenological methodology. The analysis revealed that an important difference exists in the perceptions of language as an integral part of ethno-racial diversity. For ASO professionals, language is perceived as a simple tool of communication. For Francophones living with HIV/AIDS, however, language is perceived as a way to convey sensitivity to their cultural reality and a full recognition of their Canadian citizenship. This research showed that cultural sensitivity should include a linguistic aspect when it comes to health-related services, especially in the context of an officially bilingual country.

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.